Auditoria al proceso de gestión administrativa del recurso humano y su optimización para la Cooperativa de Ahorro y Crédito 13 de abril Ltda. del Cantón Ventanas, año 2014. - Vera Calderón, Ivonne Pilar (2015)
This project is to perform a selective survey of Human Resource processes currently working in the "“Cooperativa de Ahorro y Crédito 13 de Abril LTDA.”" Canton Ventanas, its main activity Financial Intermediation, the same that allow us to optimize these processes, generate greater identity and commitment of employees and also improve the work of the company. The project is based on the different concepts of human resources, their competencies from different approaches, methodologies defining procedures, functions and ways of building the tool that is an alternative to the administration to streamline processes and improve the work of the Cooperative; placing the research methodology where the materials and methods used for data collection is specified; showing the results and discussion of the research objects to operational and administrative staff; Finally, conclusions and recommendations are synthesized, to strengthen the cooperative in relation to the planning, organization, implementation and monitoring as this entails that all together make the decision to select the right person.